Phase-transition engineered semi-metallic Cu3PdN for photothermal-enhanced cuproptosis-induced cancer therapy - Yao Gao; Guangru Li; Shuoxun Chen; Weijie Yu; Shuanglong Yi; Yu Chen; Luodan Yu (Materials Today Bio)
In-situ activation of cuproptosis shows considerable promise in cancer therapy. However, its efficacy is often hindered by the accumulation of copper ions and limitations of the activation strategy. Herein, a novel copper-palladium nitride (Cu3PdN)-modified injectable hydrogel with enhanced photothermal conversion efficiency was designed to improve copper accumulation at tumor sites and achieve photothermia-enhanced cuproptosis. A phase transition from Cu3N to Pd-doped Cu3PdN was achieved, transforming the material from a semiconductor to a semi-metal with a reduced band gap. This modification endowed Cu3PdN with full-spectrum absorption and enhanced photothermal conversion efficiency. Coupled with the abundant copper content, Cu3PdN nanoparticles hold great potential for photothermal-enhanced, in-situ cuproptosis-based cancer therapy. The Cu3PdN system demonstrates stimulus-responsive Cu(I) ions release and Fenton-like activity, promoting the generation of reactive oxygen species, mitochondrial dysfunction, and the oligomerization of dihydrolipoamide S-acetyltransferase, which together trigger cuproptosis. Overall, this study provides a promising approach for utilizing metal nitrides to induce photothermal-enhanced cuproptosis in tumor therapy.